2017
DOI: 10.4055/cios.2017.9.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Aseptic Persistent Pain after Total Knee Arthroplasty

Abstract: BackgroundPersistent pain after total knee arthroplasty (TKA) is dissatisfying to the patient and frustrating to the surgeon. The purpose of this study is to evaluate the aseptic causes and clinical course of intractable pain following TKA.MethodsOf the total 2,534 cases of primary TKA reviewed, 178 cases were classified as having aseptic persistent pain that was not resolved within 1 year after surgery. Except for the cases with periprosthetic fracture (56 knees), 122 cases of aseptic painful TKA were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…In conclusion, this exploratory pilot study identified several cytokines that exhibited higher concentrations in response to implant-related and infection-specific post-operative inflammation. Some of these cytokines have been previously implicated in chronic inflammation and infection following TKA/TKR on a systemic level [ 11 , 12 , 30 33 ], and this study confirmed this trend on a localized tissue level. Literature has already illustrated that local inflammation is much more important for early post-operative recovery for a few markers [ 6 ], and this study expanded on that knowledge to provide an extended view of inflammatory cytokines involved in tissue health.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In conclusion, this exploratory pilot study identified several cytokines that exhibited higher concentrations in response to implant-related and infection-specific post-operative inflammation. Some of these cytokines have been previously implicated in chronic inflammation and infection following TKA/TKR on a systemic level [ 11 , 12 , 30 33 ], and this study confirmed this trend on a localized tissue level. Literature has already illustrated that local inflammation is much more important for early post-operative recovery for a few markers [ 6 ], and this study expanded on that knowledge to provide an extended view of inflammatory cytokines involved in tissue health.…”
Section: Discussionsupporting
confidence: 86%
“…Properly addressing these issues is of high priority to the field of orthopaedics, especially considering the increasing demand for joint replacement [10]. Many studies have noted the pain, inflammation, and dissatisfaction that can occur following these procedures, affecting approximately 20% of patients undergoing TKA [11,12], but it is not entirely known what role cytokines play in this chronic inflammatory response. Infections, such as prosthetic joint infection (PJI), are another serious complication and are a leading cause of total joint failure [13].…”
mentioning
confidence: 99%
“…Metal-cement interface failure in cemented total knee arthroplasty with pseudotumor formation in the knee is not a common mechanism of knee implant failure and has not been reported in the literature. The de-bonding between the metal component and underlying cement could be triggered by a variety of reasons, including weak quality cement, poor cement mixing techniques, inadequate immobilization of the knee joint while the cement is curing, or inadequate cementing non-low viscosity cement use [1-2]. This interface failure can cause gradual loosening and dissociation of components with neighboring ALTR that could mimic PJI, inflammatory synovitis, or tumor formation occasionally, along with systemic signs of metallosis, but they rarely coexist [3].…”
Section: Discussionmentioning
confidence: 99%
“…Innate factors include infection, knee joint instability, application of an inappropriately sized prosthesis, loosening of the prosthesis, an abnormal lower limb stress line, stimulation by residual bone cement, and bone fracture or osteolysis around the prosthesis. 8 – 10…”
Section: Discussionmentioning
confidence: 99%